(untitled) (Journal of the College of Basic Education, 2022)
Linguists and grammarians began to collect the linguistic material after conducting comprehensive extrapolation on it. Classifying and classifying them within a structural framework based on the existence of different relationships between the components of the linguistic structure. audio, and this work is the first step in setting the rules that grammarians called (usul). They are primary and secondary assets. If the interest of grammarians in laying down the rules is in the word and its divisions (noun, verb, or letter), then the The Saracens focused their attention on setting those rules for nouns and verbs without